Influence Of Styrene Butadiene Rubber On Engineering Properties Of Soils - Hussein, Yahya Kadhim (2013)
Soil stabilization is important to the improvement of undesirable soil properties. The use of the chemical additive technique to stabilize Malaysian soils with different textures to make them more suitable for construction purposes was investigated in this study by using three soil samples, namely, poorly graded sandy soil (SP), silty sand soil (SM), and high-plasticity silty soil (MH). The soil types used were characterized and classified according to USCS using particle size distribution, plasticity, and compaction tests. The liquid chemical stabilizer styrene-butadiene rubber (SBR), produced in Malaysia as NBT II, was mixed with the soils at various percentages depending on the grain size of the soils; 6%, 8%, 10%, and 12% were used for SP, 2.5%, 5%, 7.5%, 10%, and 12.5% for SM, and 1%, 2.5%, 5%, 7.5%, 10%, and 12.5% for MH. In addition, curing times of 1, 7, 14, and 28 days were used to evaluate the effects of curing time on the soil characteristics. Shear strength tests, such as direct shear, unconfined compressive strength (UCS), triaxial, and California bearing ratio (CBR) tests, were conducted to estimate the strength properties of the soils. Consolidation and permeability tests were also performed to measure the compressibility and permeability of the soils. Temperature degrees effect on soil strength was investigated on SP soil were used 30, 50, and 100oC. On the other hand was used the spray technique to investigate the effect of spray method on density and compressive strength of soils. The results showed a decrease in the plasticity index of SM and MH, whereas no plasticity was detected in SP. The shear strength parameters (c, Øo) influenced by stabilizer addition increased the cohesion at 68.2%, 120.5%, and 8600% for MH, SM, and SP, respectively.